Jack Tumor - McGowan, Anthony (New York : Farrar, Straus and Giroux, 2009)
Fourteen-year-old Hector, suffering from severe headaches, is diagnosed with a brain tumor which speaks in his head, calling itself Jack Tumor and making an effort to improve Hector's home life, increase his popularity, and win him a girlfriend before the operation that will mean the end of one or both of them.
Keywords: Tumors -- Fiction; Sick -- Fiction; Self-actualization (Psychology) -- Fiction; Schools -- Fiction; Family life -- England -- Fiction; England -- Fiction